NAXE gene mutation-related progressive encephalopathy: A case report and literature review. Issue 42 (22nd October 2021) - Chiu, Li-Wei; Lin, Sheng-Shing; Chen, Chieh-Ho; Lin, Chien-Heng; Lee, Ni-Chung; Hong, Syuan-Yu; Chou, I-Ching; Lin, Chien-Lin; Yang, Pei-Yu
Abstract: Rationale: Progressive encephalopathy with brain edema and/or leukoencephalopathy-1 is an infantile, lethal neurometabolic disorder caused by a NAD(P)HX epimerase (NAXE) gene mutation. It is characterized by a fluctuating disease course with repeated episodes of improvement and regression. In this report, we present a rare case of NAXE gene mutation-related encephalopathy with unexpected neurological recovery and long survival time. Patient concerns: A 20-month-old girl presented with progressively unsteady gait and bilateral hand tremors after a trivial febrile illness. Her disease rapidly progressed to consciousness disturbance, 4-limb weakness (muscle power: 1/5 on the Medical Research Council scale), and respiratory failure. The patient gradually recovered 2 months later. However, another episode of severe fever-induced encephalopathy developed 2 years after the initial presentation. Diagnoses: Results of laboratory investigations, including complete blood count, blood chemistry, inflammatory markers, and cerebral spinal fluid analysis were unremarkable. Electroencephalography and nerve conduction velocity studies yielded normal results. Brain magnetic resonance imaging on diffusion-weighted imaging revealed abnormal sysmmetric hyperintensity in the bilateral middle cerebellar peduncles. A genetic study using whole exome sequencing confirmed the diagnosis of NAXE gene mutation-related encephalopathy. Interventions: Pulse therapy with methylprednisolone, intravenous immunoglobulin, coenzyme Q10, and carnitine were initially introduced. After a NAXE gene defect was detected, the vitamin B complex and coenzyme Q10 were administered. A continuous rehabilitation program was also implemented. Outcomes: NAXE gene mutation-related encephalopathy is usually regarded as a lethal neurometabolic disorder. However, the outcome in this case is better than that in the previous cases. She showed progressive neurological recovery and a longer survival time. The muscle power of the 4 limbs recovered to grade 4. At present (age of 5.5 years old), she can walk with an unsteady gait and go to school. Lessons: Although NAXE gene mutation-related encephalopathy is rare, it should be considered as a differential diagnosis of early onset progressive encephalopathy.